The Genome of the Generalist Plant Pathogen Fusarium avenaceum Is Enriched with Genes Involved in Redox, Signaling and Secondary Metabolism - Lysøe, Erik; Harris, Linda J.; Walkowiak, Sean; Subramaniam, Rajagopal; Divon, Hege H.; Riiser, Even S.; Llorens, Carlos; Gabaldón, Toni; Kistler, H. Corby; Jonkers, Wilfried; Kolseth, Anna-Karin; Nielsen, Kristian F.; et al. (PLOS ONE, 2014)
Fusarium avenaceum is a fungus commonly isolated from soil and associated with a wide range of host plants. We present here three genome sequences of F. avenaceum, one isolated from barley in Finland and two from spring and winter wheat in Canada. The sizes of the three genomes range from 41.6–43.1 MB, with 13217–13445 predicted protein-coding genes. Whole-genome analysis showed that the three genomes are highly syntenic, and share>95% gene orthologs. Comparative analysis to other sequenced Fusaria shows that F. avenaceum has a very large potential for producing secondary metabolites, with between 75 and 80 key enzymes belonging to the polyketide, non-ribosomal peptide, terpene, alkaloid and indole-diterpene synthase classes. In addition to known metabolites from F. avenaceum, fuscofusarin and JM-47 were detected for the first time in this species. Many protein families are expanded in F. avenaceum, such as transcription factors, and proteins involved in redox reactions and signal transduction, suggesting evolutionary adaptation to a diverse and cosmopolitan ecology. We found that 20% of all predicted proteins were considered to be secreted, supporting a life in the extracellular space during interaction with plant hosts.